Pattern of mean-level in personality traits and work performance of cocoa farmers in Malaysia - Nor Zaki, Nurain Syafiqah; Arif Shah, Jasmin; Sulaiman, Winorytantie; Mohamed Haris, Nur Bahiah (HH Publisher, 2024)
Since 2006, the work performance of cocoa farmers has been essential in providing more than 95% of Malaysia's cocoa production. The poor output was observed due to the poor cocoa bean output of the producers. This article aims to determine the pattern of mean level in personality traits of cocoa farmers in Malaysia that influence work performance. This research used a quantitative research method. Seven independent variables and a dependent variable were identified. A total of 357 respondents were collected. Data were collected by descriptive analysis using IBM SPSS 29. It provided the mean level of farmers' personality traits. Results revealed that farmers' decision-making (M=4.51) and discipline (M=4.63) were perceived as having a high skill level while work performance, investment, networking, problem-solving, information seeking, and risk-taking were moderate, respectively This research helps to improve understanding of the current state level of personality traits toward the work performance of cocoa farmers in Malaysia. Hence, it is recommended that the MCB formulate a policy framework that focuses on creating training modules according to the level of personality traits of farmers. These modules should be designed to consider each farmer's traits at each level. Farmers with advanced expertise possess the capacity to serve as mentors to fellow farmers. The absence of low levels in personality traits proves an opportunity for improvement.